Asian American Spring Festival 1989 Flyer 01 (SJSU Asian American Studies Department, 2024)
Asian American Spring Festival 1989 events flyer. Cultural Performers, held on Monday, April 17 and Tuesday, April 18 at 12:00 PM – 1:00 PM in the Student Union Amphitheater. Japanese Animation Nites, held on Monday, April 17 and Tuesday, April 18 at 8:00 PM – 10:30 PM in the Umunhum Room. Wednesday Nite Cinema, with a showing of "Empire of the Sun," held on Wednesday, April 19 at 7:00 – 10:00 PM in the Morris Dailey Auditorium. Hawaiian Poets, held on Thursday, April 20 at 8:00 PM – 10:30 PM in the Engineering Building, room 189. Sushi Demonstration, held on Monday, April 24 at 11:00 AM – 1:00 PM in the Student Union Upper Pad. Japanese Cultural Music Demonstration, held on Monday, May 1 at 12:00 PM – 1:00 PM in the Student Union Upper Pad. Career Panel, held on Wednesday, May 3 at 11:00 AM – 1:00 PM in the Costanoan Room. David Wong, held on Wednesday, May 17 at 12:30 PM – 1:30 PM with a reception from 4:00 PM – 6:00 PM in the Engineering Building, room 187.